If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 400 = x(x + 3) Reorder the terms: 400 = x(3 + x) 400 = (3 * x + x * x) 400 = (3x + x2) Solving 400 = 3x + x2 Solving for variable 'x'. Reorder the terms: 400 + -3x + -1x2 = 3x + -3x + x2 + -1x2 Combine like terms: 3x + -3x = 0 400 + -3x + -1x2 = 0 + x2 + -1x2 400 + -3x + -1x2 = x2 + -1x2 Combine like terms: x2 + -1x2 = 0 400 + -3x + -1x2 = 0 Begin completing the square. Divide all terms by -1 the coefficient of the squared term: Divide each side by '-1'. -400 + 3x + x2 = 0 Move the constant term to the right: Add '400' to each side of the equation. -400 + 3x + 400 + x2 = 0 + 400 Reorder the terms: -400 + 400 + 3x + x2 = 0 + 400 Combine like terms: -400 + 400 = 0 0 + 3x + x2 = 0 + 400 3x + x2 = 0 + 400 Combine like terms: 0 + 400 = 400 3x + x2 = 400 The x term is 3x. Take half its coefficient (1.5). Square it (2.25) and add it to both sides. Add '2.25' to each side of the equation. 3x + 2.25 + x2 = 400 + 2.25 Reorder the terms: 2.25 + 3x + x2 = 400 + 2.25 Combine like terms: 400 + 2.25 = 402.25 2.25 + 3x + x2 = 402.25 Factor a perfect square on the left side: (x + 1.5)(x + 1.5) = 402.25 Calculate the square root of the right side: 20.05617112 Break this problem into two subproblems by setting (x + 1.5) equal to 20.05617112 and -20.05617112.Subproblem 1
x + 1.5 = 20.05617112 Simplifying x + 1.5 = 20.05617112 Reorder the terms: 1.5 + x = 20.05617112 Solving 1.5 + x = 20.05617112 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1.5' to each side of the equation. 1.5 + -1.5 + x = 20.05617112 + -1.5 Combine like terms: 1.5 + -1.5 = 0.0 0.0 + x = 20.05617112 + -1.5 x = 20.05617112 + -1.5 Combine like terms: 20.05617112 + -1.5 = 18.55617112 x = 18.55617112 Simplifying x = 18.55617112Subproblem 2
x + 1.5 = -20.05617112 Simplifying x + 1.5 = -20.05617112 Reorder the terms: 1.5 + x = -20.05617112 Solving 1.5 + x = -20.05617112 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1.5' to each side of the equation. 1.5 + -1.5 + x = -20.05617112 + -1.5 Combine like terms: 1.5 + -1.5 = 0.0 0.0 + x = -20.05617112 + -1.5 x = -20.05617112 + -1.5 Combine like terms: -20.05617112 + -1.5 = -21.55617112 x = -21.55617112 Simplifying x = -21.55617112Solution
The solution to the problem is based on the solutions from the subproblems. x = {18.55617112, -21.55617112}
| 4(3x+1)=3(5x-4) | | R=5m+n | | 0.06(x-10)=0.03x | | 5(8x+7)=35 | | 16=p+8-5p | | T-(-16)=19 | | 10+5b=7b-10 | | b^2+14b=-48 | | 3(x-1)=2+0.5x | | 0.6x+1.2=5.4 | | -3+5x+9=47 | | x=6y-z | | 3(x+2)=2(2x-5) | | 3+6=9(2x-3) | | 20+c=4c+-7 | | T^2*p-2T*p=0 | | 2x+4+3x+23=4x+1 | | 3x+2(4x-2)+1=19 | | 5x+3(4x+2)=125 | | 0.25x=0 | | 2a+14+-7=9 | | x-11=-5x+13 | | 0.3x-0.7=0.2 | | 2x-4x+2=3 | | 2x-88=14 | | 24x+1=24x-9 | | 10a-4b=3 | | 12d-6+13=19 | | 2(2x+3)-2(x+1)=11 | | 0.4y+0.05(4-y)=1.25 | | x-1=-5x+13 | | y=5m+-1 |